Root zone nitrogen application enhances plant survival, reduces lodging, and improves grain yield of rice under submergence conditions : Nitrogen at root zone of rice under submergence condition - Alam, Saruar; Al Mamun, Md Abdullah; Talukder, Md Raihan; Bari, Md Nasimul (Annals of Bangladesh Agriculture, 2026)
Under stressful rice ecosystems, crop yield can be sustained by the use of tolerant genetic material and/or improved agronomic practices. An experiment was carried out during Aman season to assess the plant survival and productivity of rice under nitrogen (N) management during pre- and post-submergence periods. BRRI dhan52, AZ7006, and BU dhan1 were grown under 14 days of submergence (14 DS) and control conditions. Two N management strategies were used: (i) urea super granule (USG at 7 days after transplanting, DAT) and (ii) prilled urea (PU, 1/3rd at 7 DAT + 1/3rd at 7 days after de-submergence (DADS) + 1/3rd at maximal tillering stage). Plant survival, lodging, chlorophyll content in the leaves and yield component of rice were negatively impacted by submersion. Submergence for 14 days reduced dry biomass by 86.73 to 93.72% and grain yield by 18.85 to 55.12% in rice as compared to no submergence. However, the application of USG improved plant survival (91%), increased panicle bearing tillers (21 hill -1 ), improved grain fertility (73%) and decreased spikelet sterility (27%) of AZ7006 as to PU treatment. By using USG in AZ7006, a minimum loss of grain and straw yield was achieved under 14 DS. The results of this study indicate that rice yield can be increased by 25.96% through applying USG under submergence condition. Therefore, the application of USG in the root zone offers a chance to increase the rice productivity of submergence tolerant varieties under flash-flood circumstances. Ann. Bangladesh Agric. 29(2): 67-91